Genetic linkage between Huntington's disease and the DNA polymorphism G8 in South Wales families. Issue 6 (December 1985) - Harper, P S; Youngman, S; Anderson, M A; Sarfarazi, M; Quarrell, O; Tanzi, R; Shaw, D; Wallace, P; Conneally, P M; Gusella, J F
Abstract : Analysis of the polymorphism shown by the DNA probe G8 in eight South Wales families with Huntington's disease has confirmed close genetic linkage between this marker and the disorder, the most likely genetic distance being two centimorgans (cM). The closeness of the linkage suggests that G8 may have clinical applications in genetic prediction for this condition.